1991
DOI: 10.1037/0022-0663.83.4.484
|View full text |Cite
|
Sign up to set email alerts
|

Animations need narrations: An experimental test of a dual-coding hypothesis.

Abstract: In 2 experiments, mechanically naive college students viewed an animation depicting the operation of a bicycle tire pump that included a verbal description given before (words-beforepictures) or during (words-with-pictures) the animation. The words-with-pictures group outperformed the words-before-pictures group on tests of creative problem solving that involved reasoning about how the pump works. In a follow-up experiment, students in the words-withpictures group performed better on the problem-solving test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
337
2
28

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 610 publications
(392 citation statements)
references
References 16 publications
25
337
2
28
Order By: Relevance
“…However, according to the cognitive theory of multimedia learning, learners must have corresponding words and images in working memory at the same time in order to make connections between them, so simultaneous presentation should result in better learning than successive presentation. As predicted, in 8 out of 8 experiments involving computer-based lessons on pumps, brakes, lungs, and lightning, learners performed better on answering transfer questions when they received simultaneous presentation of animation and narration rather than successive presentation (Mayer & Anderson, 1991, Experiments 1 and 2a; Mayer & Anderson, 1992, Experiments 1 and 2; Mayer, Moreno, Boire, & Vagge, 1999, Experiments 1 and 2; Mayer & Sims, 1994, Experiments 1 and 2). The me-dian effect size was 1.31, which is considered a large effect.…”
Section: Five Principles For Reducing Extraneous Processingsupporting
confidence: 60%
“…However, according to the cognitive theory of multimedia learning, learners must have corresponding words and images in working memory at the same time in order to make connections between them, so simultaneous presentation should result in better learning than successive presentation. As predicted, in 8 out of 8 experiments involving computer-based lessons on pumps, brakes, lungs, and lightning, learners performed better on answering transfer questions when they received simultaneous presentation of animation and narration rather than successive presentation (Mayer & Anderson, 1991, Experiments 1 and 2a; Mayer & Anderson, 1992, Experiments 1 and 2; Mayer, Moreno, Boire, & Vagge, 1999, Experiments 1 and 2; Mayer & Sims, 1994, Experiments 1 and 2). The me-dian effect size was 1.31, which is considered a large effect.…”
Section: Five Principles For Reducing Extraneous Processingsupporting
confidence: 60%
“…In one example, students listening to an explanation of bicycle tire pump operation performed moderately well on retention tests and poorly on transfer tests; students viewing an animation on the same topic performed poorly on retention and transfer tests. On the other hand, students viewing the narrative animation performed well on both retention and transfer tests (Mayer & Anderson, 1991).…”
Section: Cognitive Load Theorymentioning
confidence: 97%
“…For example, students viewing an audiovisual presentation on soldering theory outperformed students receiving a visual-only presentation (Kalyuga et al, 1999). In addition, a series of studies performed by Mayer and his colleagues (Mayer & Anderson, 1991;Mayer & Moreno, 2002) suggested that students receiving animations with narration (on lighting formation, car braking systems, or bicycle tire pump operation) outperformed students viewing the same animation with on-screen text in recall and problem-solving transfer tests.…”
Section: Modality Effectmentioning
confidence: 99%
“…Research on visual representations has received a great deal of attention in the science education literature (Hegarty, Carpenter, & Just, 1991;Mathewson, 1999;Mayer & Anderson, 1991;Pozzer-Ardenghi & Roth, 2005). Specifically, considerable attention has been devoted to the role of representations in acquiring knowledge and understanding relationships and processes in science courses (Mandl & Levin, 1989).…”
Section: Introductionmentioning
confidence: 99%